The Relationship Between Student Authority and Discipline in Participating in Randai Extracurricular Activities at SMP N 20 Padang - Anggi Yanda, Elisa; Irmawita, Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research was motivated by the low discipline of randai extracurricular students at SMP N 20 Padang. This is thought to be caused by a lack of authority from the coach. This study aims to: (1) describe the authority of the randai extracurricular coach, (2) describe the discipline of students in participating in randai extracurricular activities, and (3) see the relationship between the authority of the coach and the discipline of students in participating in randai extracurricular activities at SMP N 20 Padang. This type of research is correlational using a quantitative approach, with the aim of revealing the relationship between the authority of the coach and the discipline of students in participating in randai extracurricular activities at SMP N 20 Padang. The population of this study were randai extracurricular students totaling 28 people and 70% were sampled, namely 20 people using the Stratified Random Sampling technique. The data collection technique used a questionnaire. The data analysis technique uses the percentage formula and rank order. The results showed that: (1) the authority of the randai extracurricular coach is low, (2) the discipline of randai extracurricular students is low, and (3) there is a significant relationship between the authority of the coach and the discipline of students in participating in Randai extracurricular activities at SMP N 20 Padang.Keywords: Authority, Student Discipline, Randai Extracurricular